Performers, trackers, lemmings and the lost: Sustained false optimism in forecasting project outcomes - Evidence from a quasi-experiment - Kutsch, Elmar; Maylor, Harvey; Weyer, Birgit; Lupson, Jonathan (Elsevier Science B.V., Amsterdam., 2011)
The consistently successful delivery of projects remains an ambition that many organisations do not achieve. Whilst the reasons behind project failure are many, one recognised factor is the ‘planning fallacy’ – over-optimism in the planning phase of a project. Whilst the planning phase of a project may be a battle for acceptance and resource allocation, the execution phase is a battle for delivery. Based on both qualitative and quantitative data gathered from a project management simulation, this study set out to establish whether optimism bias persists beyond the planning phase and into the execution phase, and, if so, to explore the reasons why. The results confirm the extent and impact of optimism bias in initial project planning. More importantly, the contribution of this study is to demonstrate on-going or sustained false opt
Keywords: MT=PROJECT